2011
DOI: 10.1177/0309133311422968
|View full text |Cite
|
Sign up to set email alerts
|

Measuring, modeling and mapping ecosystem services in the Eastern Arc Mountains of Tanzania

Abstract: In light of the significance that ecosystem service research is likely to play in linking conservation activities and human welfare, systematic approaches to measuring, modeling and mapping ecosystem services (and their value to society) are sorely needed. In this paper we outline one such approach, which we developed in order to understand the links between the functioning of the ecosystems of Tanzania’s Eastern Arc Mountains and their impact on human welfare at local, regional and global scales. The essence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…FBD [75] also reported that the EAMs exhibit rapid land cover change, having lost 11% of their primary forests and 41% of their woodland vegetation since 1975. This conversion is driven by clearance for farmland, as well as by increasing demand for timber and fuel wood [40]. This supports the argument that land cover change was caused by the deforestation of woodland vegetation.…”
Section: Fifth Principal Component: Long-term Trend Of Land Usesupporting
confidence: 75%
See 1 more Smart Citation
“…FBD [75] also reported that the EAMs exhibit rapid land cover change, having lost 11% of their primary forests and 41% of their woodland vegetation since 1975. This conversion is driven by clearance for farmland, as well as by increasing demand for timber and fuel wood [40]. This supports the argument that land cover change was caused by the deforestation of woodland vegetation.…”
Section: Fifth Principal Component: Long-term Trend Of Land Usesupporting
confidence: 75%
“…Natural forests which are predominantly located along the EAMs cover about 3%. The area of the EAMs is a globally important eco-region [38,39] and one of the world's hotspots of biological diversity [40,41]. Madoffe et al [42] reported that in the year 1900 there was three times the amount of natural forest cover compared to the 2000s.…”
Section: Study Areamentioning
confidence: 99%
“…The importance of geographic scale, spatial resolution, extent of study area, and local variations is shown by research that conveys the value of plot size in the determination of optimal soil covers in order to reduce soil runoff and loss [25]. The ecosystem services concept has been seen as a way of linking together the ecosystems of Tanzania's Eastern Arc Mountains and their impact on human welfare at multiple scales [26]. This multiscale perspective is particularly important when different stakeholders have different interests [13].…”
Section: Geographic Scalementioning
confidence: 99%
“…Hydrologically these mountains are of critical importance. Water flows from the forests throughout the year and provides services to millions of people, including c. 60% of Tanzania's electricity generation, and drinking water for at least 20% of the human population, .80% of Tanzanian industry, and much of the irrigated agriculture (Ministry of Finance and Economic Affairs, 2008;Fisher et al, 2010Fisher et al, , 2011. Most of the benefits from this water are realized far from the catchment forests where the water originates.…”
Section: Study Areamentioning
confidence: 99%